Pertumbuhan Alometri Dimensi Panjang dan Lingkar Tubuh Sapi Bali Jantan - Sampurna, I Putu; Suatha, I Ketut (Jurnal Veteriner, 2010)
Research was conducted at Bukit Jimbaran, Badung Bali from September to October 2007 to investigatethe lenght and circular body dimension of Bali cattle. Ten young male bali cattle 0.5-1.5 year old weremeasured for three times at 2 weeks interval. Collected data was analysed with regretion-corelation byallometric growth lines Y = aXb. F test and coeficient-correlation was then used to chek the validity andacurate models. Result showed that the lenght head, neck, body anterior and posterior had medium potentialgrowth. Circular neck anterior grew early with a high potential. The circular neck posterior growth potentialwas medium, where as circular thorax and abdomen was law poitential growth.
Keywords: allometric long and circular body dimension bali cattle.